METHODS OF APPLYING VARIATIVE PROGRAMS TO ASSESS THE PHYSICAL PREPAREDNESS OF PRESCHOOLERS - Zokirov Ulugbek Murodjon ogli (Proximus Journal Publishing, 2025)
The article examines the importance of variative (optional) programs in preschool educational institutions, as well as the criteria of play-based (movement-based) tests used in monitoring the physical preparedness of children and the indicators applied in their implementation.
Keywords: physical preparedness; monitoring; physical qualities; variative program